Theoretical and Practical Basis of Determining Fitness for Sports - Farkhod Turdalievich Abdullaev (Periodica Journal, 2022)
This article examines the principles of identifying strong talents and talented young people in the field of sports, as well as their proper training in order to predict their success in sports. When considering the problem of ability and talent in sports, first of all, it should be mentioned that none of the great athletes have achieved their best results by practicing independently from the beginning to the end. Specialists and trainers help to determine the competence and its correct application. The clearer and faster this process (sorting and orientation) occurs, the higher the characteristics that define sports achievements and their stability. The article also talks about the process of determining the unique physiological characteristics of athletes
Keywords: flexibility; athletics; stage; sports